San Diego's Hysterical History - Lockwood, Herbert frey50; Edited by William Carroll (Raton, New Mexico Coda Publications, 2003)
"San Diego's Hysterical History" is "Fallout From the Skeleton's Closet" written years ago by talented local newspaper editor Herber Lockwood.
Keywords: History--California--San Diego